Quantitative characterization and analysis of pore-fractures in tar-rich coal under high-temperature pyrolysis based on micro-CT imaging - Yang, Fu; Jiang, Pengfei; Duan, Zhonghui; Cheng, Zhongyan; Wang, Zhendong (Frontiers in Earth Science, 2023)
To investigate the pore distribution characteristics and permeability behavior of tar-rich coal after high-temperature pyrolysis at 500 ℃ , X-ray computed tomography (CT) scanning was employed on coal samples that had been cooled to room temperature following pyrolysis at 500 °C. A total of 1755 cross-sectional slices were obtained and utilized for three-dimensional reconstruction. Subsequently, the compositional constituents of the tar-rich coal were extracted, and the distribution features of connected and isolated pores were determined using the axial algorithm. Geometric parameters of the pores were computed using relevant algorithms. In order to explore the permeability characteristics of coal samples after pyrolysis at high temperature, an equivalent Pore Network Model was established for the tar-rich coal, and its parameter indicators were analyzed. Research results reveal that the post-pyrolysis pore distribution characteristics of the tar-rich coal exhibit non-uniformity, with a significant scale of pore size distribution. Pores tend to display a concentrated distribution pattern in the spatial domain. The total porosity is 14.24%, with connected pores accounting for 12.34%. Two Representative Elementary Volume (REV) regions were selected. Most pore widths in these regions range from 10-50 μm, and the peak interval of pore lengths falls within 20-60 μm, accounting for over 40% of the total. Additionally, the peak range of pore surface area is 200-100 μm², similarly comprising over 40% of the total. Distinct characteristics were revealed by the constructed Pore Network Model (PNM) for the two REV. In REV-1, the pore network appears to be in an early developmental stage, exhibiting poor connectivity. On the other hand, in REV-2, the pore network is well-developed, with a coordination number histogram displaying a bimodal structure. Pores with coordination numbers exceeding 6 account for approximately 50% of the total pore population, indicating strong connectivity.